Gender Differences in the Intergenerational Earnings Mobility of Second-Generation Migrants - Regina Flake (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
This study analyzes gender diff erences in the intergenerational earnings mobility of second-generation migrants in Germany. The analysis takes into account potential influences like assortative mating in the form of ethnic marriages and the parental integration measured by parents' years since migration. First, intergenerational earnings elasticities are estimated at the mean and along the earnings distribution. The results do not reveal large differences in the intergenerational mobility - neither between natives and migrants nor between men and women. Second, intergenerational changes in the relative earnings position are analyzed. The results show that migrants are less likely than natives to worsen their relative earnings position while they have the same probability as natives to improve their earnings position. In summary, migrants are mostly as (im)mobile as the native population. – – Diese Studie analysiert geschlechtsspezifische Unterschiede in der generationsübergreifenden Einkommensmobilität von Zweitgenerationseinwanderern in Deutschland. Die Analyse berücksichtigt explizit Einflüsse wie das Heiratsverhalten von Migranten oder die elterliche Integration gemessen in Jahren seit der Einwanderung. Zunächst werden durchschnittliche generationsübergreifende Einkommenselastizitäten geschätzt. Diese Schätzungen werden durch Quantilsregressionen ergänzt. Die Ergebnisse zeigen keine großen Unterschiede in den Einkommenselastizitäten - weder zwischen Einheimischen und Migranten noch zwischen Männern und Frauen. Anschließend werden Veränderungen der relativen Einkommenspositionen analysiert. Es wird gezeigt, dass Migranten eine geringere Wahrscheinlichkeit als Einheimische haben, ihre relative Einkommensposition zu verschlechtern, während sie die gleiche Wahrscheinlichkeit haben, ihre Einkommensposition zu verbessern. Insgesamt sind Migranten zumeist genauso (im)mobil wie die einheimische Bevölkerung.
Keywords: F22; J12; J30; J62; 330; International migration; second-generation migrants; intergenerational mobility; marriage; International migration; second-generation migrants; intergenerational mobility; marriage